Pengaruh pembangunan infrastruktur jembatan terhadap kualitas air permukaan di ruas jalan Mameh-Windesi - Emma Manjauna; Markus H. Langsa; Hendri Hendri (Program Pascasarjana Universitas Papua, 2023)
ABSTRACT: Infrastructure development including the construction of bridges and roads of Trans Papua lines, especially on the Mameh-Windesi section in Manokwari Selatan and Teluk Wondama regency has the potential to reduce environmental quality. The purpose of this study was to determine the impact of the bridge’s construction on the water quality at the bridge construction sites. The impact was measured based on the river capacity to receive the contaminants from the construction activities determined by the quality status of river water using the STORET method. The bridge of Mawin 5 and 6 was selected for this study. The total score for the STORET method for the river at the Mawin 5 and 6 is -10 and -8, respectively. Therefore, the river water’s is categorized as lightly polluted according to Peraturan Menteri Lingkungan Hidup No. 115 of 2003. The high concentrations of suspended solids and turbidity on the river waters after the construction was due to the remnants of construction materials entering the rivers as well as the high surface run off. The impact of bridge development on the quality of surface water with the increase of suspended solid and turbidity in the construction sites was temporary with only physical parameters of water impacted.